Wie viel Europa braucht die Energiewende? - Erik Gawel; Sebastian Strunz; Paul Lehmann (Helmholtz-Zentrum für Umweltforschung (UFZ), 2014)
– It is often argued that Germany's energy transition (the so-called Energiewende) needs to be Europeanized, so as to make the transition process more efficient. In particular, the German system of feed-in tariffs for renewables is criticized for being an obstacle to efficient European energy supply. However, we point out that Germany's approach is no outlier but rather well embedded in the European context of heterogeneous energy policies. Also, full centralization of energy policy decisions on the EU-level is neither desirable from an economic point of view nor a politically feasible option. Against this background, we identify priorities for fostering the European dimension of the Member States' energy policies, such as the coordination of grid extensions and capacity markets.
Keywords: 330